2(a-2)=-(a-1)/(a-4)

Simple and best practice solution for 2(a-2)=-(a-1)/(a-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(a-2)=-(a-1)/(a-4) equation:


D( a )

a-4 = 0

a-4 = 0

a-4 = 0

a-4 = 0 // + 4

a = 4

a in (-oo:4) U (4:+oo)

2*(a-2) = -((a-1)/(a-4)) // + (a-1)/(a-4)

2*(a-2)+(a-1)/(a-4) = 0

(2*(a-2)*(a-4))/(a-4)+(a-1)/(a-4) = 0

2*(a-2)*(a-4)+a-1 = 0

2*a^2-11*a+15 = 0

2*a^2-11*a+15 = 0

2*a^2-11*a+15 = 0

DELTA = (-11)^2-(2*4*15)

DELTA = 1

DELTA > 0

a = (1^(1/2)+11)/(2*2) or a = (11-1^(1/2))/(2*2)

a = 3 or a = 5/2

(a-5/2)*(a-3) = 0

((a-5/2)*(a-3))/(a-4) = 0

((a-5/2)*(a-3))/(a-4) = 0 // * a-4

(a-5/2)*(a-3) = 0

( a-3 )

a-3 = 0 // + 3

a = 3

( a-5/2 )

a-5/2 = 0 // + 5/2

a = 5/2

a in { 3, 5/2 }

See similar equations:

| X^2(5x+3)=26x | | 4x-4=2x+14 | | 1/3+2x=5/12 | | 8X-5Y-3=0 | | 50=9x+5 | | 3(2x-1)=2(4x-7) | | 0.3x+33.6=51 | | 7x-10=x+2 | | 7.3x-5.8+2.5x= | | F(x)=2x^2+5x+9 | | 56=24(1/6z+5/6) | | 8x=27-x | | H=-16t^2+72t+3 | | -38.5=4.3z-4.1 | | 2x+4-3x=9 | | 24-2x=-6x+4 | | 2x+6-5x=-3 | | 3.1=1.3+2.9 | | 16=20(1/5z+4/5) | | H=-16t+72t+3 | | 5x+2-3x=-2 | | (X+4)(5x-1)=0 | | 3x+6-4x=8 | | a^2=135+6a | | 3x+4-2x=9 | | 38x-13=5(7x-1)+3x-8 | | -6x=-4x-16 | | (x+3)(x+6)+(x+3)(x+6)= | | 3x-5-6x=4 | | 7(z+3)-5z=9 | | 5(5-y)/3=y | | Y^2/30=y/15+1/2 |

Equations solver categories